مدى إمكانية تطبيق معيار المحاسبة ISA 7 في شركة المدار الجديد - العالممختار النعمي السائح (Aljameai, 2025)
المستخلص: هدفت هذه الدراسة إلى التعرف على مدى إمكانية تطبيق معيار المحاسبة الدولي رقم 7 (ISA 7) في شركة المدار الجديد، Abstract: This study aimed to explore the feasibility of implementing International Accounting Standard 7 (ISA 7) at Al-Madar Al-Jadeed Company through interviews with the Chief Financial Officer (CFO) and the Internal Audit Manager. It was found that the company primarily follows local accounting standards, with partial adoption of international practices. The main challenges identified include legal restrictions preventing full implementation of ISA 7, as well as difficulties in classifying cash flows into operational, investment, and financing activities. The study also revealed gaps between the local accounting system and international requirements, necessitating updates to the accounting system if legal approval is granted for the adoption of international standards. Additionally, a lack of specialized training on ISA 7 was observed. Based on the findings, recommendations were made to develop a comprehensive training plan for staff, engage with legislators to amend legal frameworks, and update accounting procedures to align with international standards to improve financial transparency and increase trust in financial reports.